Moderating role of product involvement on the relationship between brand personality and brand loyalty - Lada, Suddin; Md. Sidin, Samsinar; Teoh, Kenny Guan Cheng (Array Development, 2014)
Drawing from observations by consumer behavior theorists and product involvement studies, the present study seeks to investigate the moderating role of product involvement on the relationship between brand personality and brand loyalty. A total of 958 respondents participated in this study. They completed a 14-items questionnaire to measure product involvement, and a 32-items and 16-items questionnaire to measure brand personality and brand loyalty respectively. Results suggest that the effect of product involvement related to brand personality and brand loyalty is partly moderated, where the impact is greater for low involvement consumer groups than for moderate and high involvement consumer groups for both dimensions of ‘excitement’ and “ruggedness’. The present study has also revealed that product involvement increases the direct effect of excitement and ruggedness of brand personality dimension on brand loyalty. However, product involvement decreases the direct effect of sincerity, competence, and sophistication of brand personality dimension on brand loyalty. The study provides support for the value of measuring product involvement in the sportswear industry. Furthermore, marketing efforts for sportswear companies need to distinguish between the elements of involvement that are more significant to brand personality and bran loyalty. The study also expands the body of knowledge by providing empirical verification of the link among product involvement profile (i.e., pleasure, interest, sign, risk importance, and risk probability), brand personality, and brand loyalty.